2015
DOI: 10.1080/17439760.2015.1048815
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of relational catalyst support of goal strivings

Abstract: The goal of this work was to test a theoretical model of relational catalyst support provision that promotes thriving in non-adverse times. We tested a pathway proposed by Feeney and Collins (2014) that explains how relational catalyst support in the context of close relationships might lead to thriving. We proposed that once relational catalyst support has been received, it functions through the mechanisms of being perceived to be responsive to one’s needs and promoting perceived capability. Perceived capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 45 publications
6
33
1
3
Order By: Relevance
“…One other paper has been published with this daily diary dataset (Feeney & Lemay, 2012; Study 1). Additionally, one other paper has been published with the same sample but with data other than the daily diary (Tomlinson, Feeney, & Van Vleet, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…One other paper has been published with this daily diary dataset (Feeney & Lemay, 2012; Study 1). Additionally, one other paper has been published with the same sample but with data other than the daily diary (Tomlinson, Feeney, & Van Vleet, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Research aimed at testing a model of relational support for thriving [7] showed that partner support of goal strivings predicted thriving over time through increasing feelings of capability and perceived partner responsiveness [48]. Also, a study designed to examine relational influences on decisions to embrace or forego challenging life opportunities revealed that spousal support encouraged decision-makers to accept the challenge, and this decision predicted long-term thriving [49].…”
Section: Support For Exploration and Pursuit Of Opportunitiesmentioning
confidence: 99%
“…This parental role also appears to extend to enabling thriving in adolescents, where parents may provide guidance in relation to an adolescent's schooling (see, e.g., Theokas et al, 2005) and financial support for the child to access facilitative opportunities and resources (see, e.g., Weine et al, 2013). More recent investigations have broadened extant research on family support to include the role of spouses in promoting thriving (see, Sarkar & Fletcher, 2014;Tomlinson, Feeney, & Van Vleet, 2016). Within these studies, partners were suggested to alleviate strain caused by time-related work pressures (Sarkar & Fletcher, 2014) and that their support acted as a relational catalyst for thriving through the support of goal strivings (Tomlinson et al, 2016).…”
Section: Family Supportmentioning
confidence: 99%